2020
DOI: 10.1111/apa.15717
|View full text |Cite
|
Sign up to set email alerts
|

Hip contractures were associated with low gross motor function in children with cerebral palsy

Abstract: Aim The aim was to identify the prevalence of hip contractures and their association with gross motor function and pain in the lower extremities among Danish children with cerebral palsy (CP). Methods This cross‐sectional study was based on data collected during regular clinical examinations in 2018–2019 and registered in the National Danish Clinical Quality Database of children with CP. The study population was 688 children (59% boys) aged five to 12 years across all Gross Motor Function Classification System… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Our finding of GMFCS levels IV–V being associated with a higher prevalence of ankle contracture compared to GMFCS levels I–III is substantiated by Østensjø et al 18 who found that children with GMFCS levels I and II had significantly fewer deviations in ROM in the lower extremities, hip, knee and ankle, than children with GMFCS levels III–IV. Besides, two other studies found that a higher GMFCS level was associated with respectively knee contracture 7 and hip contracture 12 …”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Our finding of GMFCS levels IV–V being associated with a higher prevalence of ankle contracture compared to GMFCS levels I–III is substantiated by Østensjø et al 18 who found that children with GMFCS levels I and II had significantly fewer deviations in ROM in the lower extremities, hip, knee and ankle, than children with GMFCS levels III–IV. Besides, two other studies found that a higher GMFCS level was associated with respectively knee contracture 7 and hip contracture 12 …”
Section: Discussionmentioning
confidence: 96%
“…Besides, two other studies found that a higher GMFCS level was associated with respectively knee contracture 7 and hip contracture. 12 It is a strength of this study that it includes data on a total population of children with a confirmed CP diagnosis at all GMFCS levels aged 6 to 14 years from a national registry with high coverage. Given the prevalence and distribution of sex, GMFCS levels and muscle tone of the plantar flexors, our study population is likely to be representative of children with CP in the same age group in other countries with similar treatment options as in the CPOP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, contracture of the calf muscle causes ankle flexion or equinus posture of the foot, which negatively affects standing, balancing, and walking. Contracture of the pelvic floor muscle results in hip flexion deformity [13][14][15]. Interventions are therefore concentrated on enhancing lower limb posture, which is expected to improve balance and gait.…”
Section: Introductionmentioning
confidence: 99%